The vintage caper [large type] - Mayle, Peter (Mayle, Peter. Sam Levitt mysteries., 2010)
After inviting the Los Angeles Times to his impressive wine cellar to write an extensive piece on the treasures of his collection, Hollywood lawyer Danny Roth finds himself the victim of a world-class wine heist. Enter Sam Levitt, former corporate lawyer, wine connoisseur, and expert on cultivated crime. Called in by Roth's insurance company, Sam follows his leads - first to Bordeaux's magnificent vineyards and then to the wine collectors of Provence. (Bestseller)